RECONSTRUCTION ABILITIES OF ACOUSTIC EMISSION METHOD AT CHANGES OF STRAIN-DEFORMATION STATE OF METASANDSTONES OF THE KRYVYI RIG SUPER-DEEP MINING HOLE - PRODAIVODA, G.; ONANKO, A.; SHABATURA, O.; ONANKO, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Effect of acoustic emission under laser thermal-mechanical strains in sandtones are investigated. Elastic waves pulses are discovered from microfractures that of probably connected with elastic balance in sandstones.